A review on safety improvements in Malaysian construction industry: article - Hanif, Siti Fatimah; Jafri, Hasnora (2017)
The construction industry is one of the most hazardous industries in the world. The importance of safety in the construction industry is often overlooked, as people tend to focus more on getting the job done in time rather than getting it done safely. Malaysia’s construction industry is no different, as represented by the amount of accidents related to construction that has occurred in the past year. The purpose of this research paper is to review the safety improvements in Malaysian construction industry. The main objectives of the study is to review the development of safety in the local construction industry as well as analyze the safety improvements used worldwide that can be implemented in the Malaysian construction industry. The statistics of the accidents relating to construction was reviewed, along with the causes of fatalities and high number of injuries resulting from accidents in the construction industry. Several accident causation theories were also discussed in order to gain an in-depth understanding the causes of accidents and consequences of hazards, as well as accident prevention measures. Interviews and questionnaires were conducted in order to obtain an indepth understanding of the safety practices in the Malaysian construction industry. The questionnaires were designed to evaluate the safety performance of the construction industries by studying them through four main aspects; safety climate, safety culture, safety attitude, and general safety measures. The variations of the safety performance practice by different sized companies as well as different levels of employment in the organization are compared and analyzed according to the four aspects. From the results obtained, the responsibility of the management towards the involvement of their employees as well as self-awareness in safety greatly affects the safety performance of an organization, thus, facilitates the improvement of high safety performance in the construction industry